Erzaehltechniken und Informationsvergabe in Vasilij Aksenovs Ožog, Zolotaja naša železka und Poiski žanra - Kessler, Stephan (Slavistische Beitraege, 1998)
In the series Slavonic Contributions Slavic dissertations of German-speaking countries as well as occasionally also American, English and Russian are published. In addition, the series provides a forum for anthologies and monographs of established scientists.